Synthesis, characterization and mass-spectrometric analysis of [LSn(IV)F4−x]x+ salts [L = tris ((1-ethyl-benzoimidazol-2-yl)methyl)amine, x = 1–4]. Issue 46 (14th November 2018) - Suter, Riccardo; Swidan, Ala'aeddeen; Zijlstra, Harmen S.; Macdonald, Charles L. B.; McIndoe, J. Scott; Burford, Neil
Abstract : A series of cationic tin fluoride complexes has been synthesized by successive fluoride abstraction from SnF4 with TMSOTf in the presence of the tetradentate nitrogen donor BIMEt3 . Abstract : A series of complexes with the formulae [(BIMEt3 )SnF4− x ][OTf] x with x = 1–4 has been synthesized by successive fluoride abstraction from SnF4 with TMSOTf in the presence of the tetradentate nitrogen donor BIMEt3 (tris ((1-ethyl-benzoimidazol-2-yl)methyl)amine). Single crystal X-ray diffraction and heteronuclear NMR spectroscopic analysis provided insight into these new main group cations. Electrospray ionization mass spectrometric analysis on solutions containing the different salts allowed for successful detection of the cations [(BIMEt3 )SnF] 3+, [(BIMEt3 )SnF2 ] 2+ and [(BIMEt3 )SnF3 ] + .